2008
DOI: 10.1111/j.1460-9568.2008.06208.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cold exposure increases RGS7 expression and decreases α2‐autoreceptor‐mediated inhibition of noradrenergic locus coeruleus neurons

Abstract: Chronic stress exposure alters the central noradrenergic neurons originating from the locus coeruleus (LC). Previously, we demonstrated that evoked increases in the firing rate of LC neurons and their release of norepinephrine are enhanced following chronic cold exposure. In the present studies, we tested the hypothesis that reduced feedback inhibition of LC neurons might underlie these alterations in LC activity by examining the effect of alpha(2)-autoreceptor stimulation on LC activity in chronically stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 75 publications
0
24
1
1
Order By: Relevance
“…Another recent study also showed that RGS7 was upregulated when animals were stressed by chronic exposure to cold. 132 The detected increase of the RGS7 signal on the immunoblot was only about 20%, but was appreciable particularly because RGS4 and RGS2 levels did not change in the same preparations. Noteworthy, there was no corresponding increase in Gβ5 levels, although the reason for this is unclear.…”
Section: Expression and Subcellular Localization Of Gβ5–r7 Proteinsmentioning
confidence: 87%
See 2 more Smart Citations
“…Another recent study also showed that RGS7 was upregulated when animals were stressed by chronic exposure to cold. 132 The detected increase of the RGS7 signal on the immunoblot was only about 20%, but was appreciable particularly because RGS4 and RGS2 levels did not change in the same preparations. Noteworthy, there was no corresponding increase in Gβ5 levels, although the reason for this is unclear.…”
Section: Expression and Subcellular Localization Of Gβ5–r7 Proteinsmentioning
confidence: 87%
“…133 The recent study of Jedema and colleagues indicates that the elevation of RGS7 attenuates signal transduction via the α2-adrenergic receptors in rat locus coeruleus, the area of the brain involved in stress. 132 These presynaptic Gi-coupled receptors provide negative feedback to the process of norepinephrine release. In this model, upregulation of RGS7 under conditions of chronic stress attenuates signaling via the α2-adrenegic receptors by accelerating the GTPase activity of Gi, which would result in a restoration of the system's ability to respond to subsequent stimuli.…”
Section: Expression and Subcellular Localization Of Gβ5–r7 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…72,73 Chronic stress also downregulates 5-HT 1A autoreceptors within the DRN. 74,75 It is not known how long such adaptations may persist after recovery but our findings are nevertheless consistent with the putative role of stress in the physiopathology of addiction.…”
Section: Discussionmentioning
confidence: 98%
“…However, RGS7 is likely acting through a signaling cascade that is separate from the 5-HT 1A R-AC axis as it did not appear to play a compensatory role in the absence of RGS6 (22), and RGS7 was not able to modulate 5-HT 1A receptor signaling in vitro (65). In addition, RGS7 is also upregulated in the locus coeruleus (LC) of the mouse following chronic stress induced by cold exposure and is responsible for modulating the ability of the α 2 -autoreceptor to inhibit neuronal firing and release of norepinephrine (66). Finally, there is evidence suggesting that RGS9 may play a modulatory role in anxiety as RGS9-2 expression is upregulated in the NAc in response to a mouse model neuropathic pain.…”
Section: Anxiety and Depressionmentioning
confidence: 99%